A Qualitative Study of Online Disinhibition and Parasocial Bonds Among ‎Indian Adolescents - Kavita Sharma; Manju Gera‎ (Digital Learning, Social Science, and Life-course Studies, 2025)
This study explores the impact of the Online Disinhibition Effect (ODE) and Parasocial Attachment (PSA) on Indian adolescents' emotional expression, behavior, and identity formation in digital environments. Through a combination of reflective journals and semi-structured interviews with 42 adolescents, the research examines how ODE influences self-expression, emotional release, and the development of parasocial bonds with media figures. Findings reveal that ODE significantly enhances emotional freedom and self-expression online, leading to the formation of parasocial relationships, which act as emotional substitutes for real-life interactions. These relationships were found to play a critical role in adolescents’ identity exploration and emotional regulation, particularly in the context of Indian cultural values such as collectivism and family dynamics. The study also identifies the emotional validation through social media engagement as a key mediator in the development of PSA. The results highlight the complex interplay between online disinhibition, parasocial connections, and adolescent development, providing new insights into the role of digital platforms in shaping adolescent identities in non-Western contexts. The study contributes to the literature on digital behavior, identity formation, and cultural influences on online interactions, offering practical implications for media literacy and digital emotional intelligence in educational settings. Future research should expand the sample to include diverse socioeconomic backgrounds and employ longitudinal methods to explore the long-term effects of ODE and PSA.